Soil Infiltration Variability Mappping: Kuala Lumpur - Chan, Shen Sam (Universiti Sains Malaysia, 2006)
The government has developed new guidelines to designer of stormwater management since 1990’s. The Malaysian Stormwater Management Manual (MSMA) introduced new method in controlling rainfall runoff by source control. The result is a controlled runoff considering both quantity and quality. Infiltration is an important tool in visualizing the objectives of MSMA. This study addresses the spatial variability of infiltration rates in the area of Kuala Lumpur. The study is base on site investigation reports on 55 locations, which means this is an off-site study. Borehole log and laboratory results provide data in soil type decision making. The steady state infiltration rate is base on USDA study recommendations. Contour maps is then prepared by using SURFER surface mapping programme. The infiltration variability map shows a few possible potential infiltration practicing area, namely National Theatre, Hospital Kuala Lumpur, Bricksfield HQ, DBKL club, Jalan Bukit Bintang, Cheras Batu 2 ½. A geostatistical analysis was performed to investigate spatial autocorrelation of infiltration data using GS+ software. This study do not provide exact value of infiltration contour. It is a result of study references and recommendation value.